2019
DOI: 10.1007/s42452-019-1359-6
|View full text |Cite
|
Sign up to set email alerts
|

Bending, buckling and free vibration of nonlocal FG-carbon nanotube-reinforced composite nanobeams: exact solutions

Abstract: This paper investigates the bending, buckling and free vibration behaviors of functionally graded carbon nanotubereinforced composite (FG-CNTRC) nanobeams by considering small-scale effect. The governing equations of motion of a Timoshenko beam under a general loading are derived utilizing the nonlocal elasticity theory. The equations governing bending and stretching behavior of CNTRC nanobeams are uncoupled to a fifth-order ordinary differential equation with respect to the rotation of cross-section for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Nonlocal phenomena resulted in a reduction in the critical buckling load, while increasing CNT volume fraction in the beam increased the critical buckling load. Borjalilou et al 107 and Thang et al 108 have conducted studies that indicate opposite trends for deflection and frequencies of beams and plates. In a study by Daghigh et al, 109 the effect of temperature and nonlocal parameter on Young's modulus and natural frequency of CNT composite nanoplates was examined, revealing a reduction of 16—30% and 1—2 %, respectively, with a temperature change of 100 o .…”
Section: Modelling Methodologymentioning
confidence: 99%
“…Nonlocal phenomena resulted in a reduction in the critical buckling load, while increasing CNT volume fraction in the beam increased the critical buckling load. Borjalilou et al 107 and Thang et al 108 have conducted studies that indicate opposite trends for deflection and frequencies of beams and plates. In a study by Daghigh et al, 109 the effect of temperature and nonlocal parameter on Young's modulus and natural frequency of CNT composite nanoplates was examined, revealing a reduction of 16—30% and 1—2 %, respectively, with a temperature change of 100 o .…”
Section: Modelling Methodologymentioning
confidence: 99%
“…They showed that the deflection of the plates diminished with an increase of the elastic modulus. Static/dynamic bending and buckling behavior of nonlocal FG-SWCNT-reinforced composite nanobeams with consideration of the Timoshenko beam model was investigated by Borjalilou et al [385]. The governing relations were decoupled to an ordinary differential relation with the fifth-order pertinent to the cross-section rotation associated with the static bending as well as buckling.…”
Section: Linear Static Bending Of Micro/nano-structuresmentioning
confidence: 99%
“…Galerkin of weighted residual handles circular plate vibration problem without any manipulation of governing equation with very precise results compared to experimental with few iterations. Other recent publications reported on vibration are [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 96%